2016
DOI: 10.1016/j.pedneo.2015.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Intracardiac Thrombosis in the Right Atrium and Superior Vena Cava in Critically Ill Neonates who Required the Installation of a Central Venous Catheter

Abstract: This study allowed us to identify several contributing factors to the development of intracardiac thrombosis in the RA and SVC related to the installation of a CVC in a subgroup of critically ill neonates. Multicenter and well-designed studies with a larger number of patients could help validate our findings and/or identify other risk factors that were not identified in the present study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…The mean duration of surgery was 316 ± 133 minutes. Children were ventilated for a median of 0 [0, 2] days, and the length of duration stay on ICU was a median of 3.00 1,6 days (Table 1). No relevant bleeding was documented in association with the placement of the CVC, and no arterial punctures were noted.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean duration of surgery was 316 ± 133 minutes. Children were ventilated for a median of 0 [0, 2] days, and the length of duration stay on ICU was a median of 3.00 1,6 days (Table 1). No relevant bleeding was documented in association with the placement of the CVC, and no arterial punctures were noted.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have reported that CADVT occurs in approximately 15%–39% of pediatric patients with a CVC and the risk is particularly high in preterm infants and neonates 9,10 . It must be noted, that the inflammatory and immunosuppressive effects of cardiopulmonary bypass and major surgery may have a different impact on the occurrence of complications in such patients when compared with other conditions 5,6 . Furthermore, the question of the influence of the puncture site of a CVC on the development of CADVT for pediatric cardiac surgery patients has not been conclusively answered in studies.…”
Section: Introductionmentioning
confidence: 99%
“…Table 5 The analysis between the two groups endothelial cells, suppression of fibrinolysis with increased levels of plasminogen activator inhibitor-1 (PAI-1), and a decrease in inhibitory protein levels contribute to thrombus formation [20,21]. Infections have been reported as a risk factor in many studies [4,7,9,15,[22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Saracco et al revealed in their study, in which they examined 75 neonates with thrombi, that 16% of thrombi were ICT [36]. Sepsis, CVC, CHD, prematurity, RDS, and gestational diabetes are the most significant risk factors [16,20,[22][23][24]36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation